Conceptual proximity and the experience of war in Siegfried Sassoon’s ‘A working party' - Giovanelli, Marcello (John Benjamins, 2014)
Santanu Das (2007) has argued that the defining characteristics of first-world war poetry are the stark movement away from epic forms, and the refashioning of verse as a type of ‘missive from the trenches’, both of which shift the perspective of the reading experience from distance to proximity. In this chapter, I offer a way of explaining this interpretation both generally, and specifically through analysing Siegfried Sassoon’s (1917) ‘A Working Party’. My analysis focuses on the distribution of complex temporal and atemporal profiles, the texture afforded by reference point relationships and the subsequent authorial manipulation and control over dominions, and the point-of view effects associated with pronoun use. I suggest that paying close attention to these can explain a reading experience that illuminates at close-hand the horrific intimacy of the trench.